Revolutionising Organisational Safety and Health Management in the Nigerian Manufacturing Industry via Active Employee Involvement - Olokede, Bolatiwa Adunni; Ukpere, Wilfred (Journal of Economic Development, Environment and People, 2023)
The concerns with the increasing rate of preventable accidents occurrences in Nigeria's manufacturing sector required a renewed focus on occupational safety and health (OSH). Specifically, despite the number of interventions and the amount of spending on interventions, the effects have remained minimal. Also, despite the efforts of researchers and their suggestions, little or no impact has been noticed as OSH continues to be inadequate. These problems call for a fresh approach and consultation with the individuals who will be utilising these solutions most directly (the workers) to address these issues at their core. This paper is part of a large mixed-method study designed to explore how to improve the efficacy of OSH in Nigeria. However, this present paper reports part of the initial phase as it examines the perception of blue-collar workers in the Nigerian industry to understand how well the existing measures have satisfied their safety needs from the standpoint of available human resource management practices (HRM practices). Hence, this work uses a cross-sectional research design to gather data from both registered and non-registered workplaces located in cities in three Nigerian states, totalling 633 required participants. A mix of simple random and convenience sampling techniques was applied to select the expected samples. SPSS software version 26 was used to analyse the 641 responses. The blue-collar workers constituted the unit of analysis for this phase. The findings indicated that there are diverse opinions among Nigerian manufacturing blue-collar workers regarding the accessibility and applicability of the HR practices under investigation. Based on the findings, recommendations for improving OSH practices in the manufacturing industry is suggested with the hope of maximising employee involvement in strengthening the efficacy of OSH interventions in Nigerian manufacturing workplaces.